Переваги і недоліки політики мультикультуралізму - Волошенюк, О. В.; Volosheniuk, O. V.; ORCID: http://orcid.org/0000-0001-8978-0645; ResearcherID: J-7042-2016 (Форум права. – 2019. – № 3 (56). – С. 6-12, 2019)
Проаналізовано наукові підходи до розуміння сутності політики мультикультуралізму. Розкрито позитивні та негативні наслідки вказаної політики з урахуванням наявного закордонного досвіду. Встановлено, що критики політики мультикультуралізму звертають увагу на те, що вона руйнує єдність суспільства, обмежує права культурної більшості, породжує серед мігрантів феномен власної переваги тощо. Доведено, що політика мультикультуралізму має потужний демократичний потенціал, оскільки вона створює реальні умови неконфліктного співіснування різних культурних груп у межах території держави. Наголошено на тому, що політика мультикультуралізму є ефективним інструментом вирішення проблеми співіснування культур за умови пошуку нових форм і методів її реалізації з урахуванням національних та історичних особливостей розвитку кожного суспільства. Зроблено висновок стосовно доцільності впровадження політики мультикультуралізму в Україні.

Policies of multiculturalism are one of the options for solving the problem of peaceful coexistence of representatives of different cultures on the state territory. Despite a large number of publications on the problems of multiculturalism, the social sciences and humanities do not have a single position on the meaning of this category, as well as the appropriateness of introducing a corresponding state policy in modern conditions. The object of research is social relations that determine the features of coexistence of representatives of different cultures on the state territory. The subject of research is the advantages and disadvantages of multiculturalism policy. The purpose of the article is to reveal the positive and negative consequences of the policies of multiculturalism, taking into account the achievements and mistakes of its implementation in the leading countries of the world. The need to achieve the purpose of the study led to the use of so methods of cognition as formal-logical, systemic, historical, critical and comparative. The scientific approaches to understanding the essence of the policy of multiculturalism are analyzed. The positive and negative consequences of this policy were revealed taking into account the existing foreign experience. It has been established that critics of the policy of multiculturalism draw attention to the fact that it destroys the unity of society, restricts the rights of the cultural majority, and creates preconditions for the emergence of intercultural conflicts and so on. It is proved that the policy of multiculturalism has a strong democratic potential since it creates real conditions for non-conflicting coexistence of different cultural groups. It is concluded that the policy of multiculturalism remains an effective tool for solving the problem of coexistence of cultures subject to search for new forms and methods for its implementation taking into account national and historical peculiarities of the development of each society. The practical value of the work lies in the fact that the substantiated provisions and conclusions in it deepen the scientific knowledge of multiculturalism politics. The obtained results can be used in the process of teaching the theory of state and law, comparative law and in solving practical problems related to the process of improving intercultural dialogue in Ukraine.

Проанализированы научные подходы к пониманию сущности политики мультикультурализма. Раскрыты положительные и негативные последствия указанной политики с учетом имеющегося зарубежного опыта. Установлено, что критики политики мультикультурализма обращают внимание на то, что она разрушает единство общества, ограничивает права культурной большинства, порождает среди мигрантов феномен собственного превосходства и тому подобное. Доказано, что политика мультикультурализма имеет мощный демократический потенциал, поскольку она создает реальные условия неконфликтного сосуществования различных культурных групп в пределах территории государства. Отмечено, что политика мультикультурализма является эффективным инструментом решения проблемы сосуществования культур при поиске новых форм и методов ее реализации с учетом национальных и исторических особенностей развития каждого общества. Сделан вывод о целесообразности внедрения политики мультикультурализма в Украине.
The advantages and disadvantages of multiculturalism politics
Волошенюк, О. В. Переваги і недоліки політики мультикультуралізму [Електронний ресурс] / О. В. Волошенюк // Форум права. – 2019. – № 3 (56). – С. 6-12. – Режим доступу: http://forumprava.pp.ua/files/006-012-2019-3-FP-Voloshenyuk_3.pdf.
Волошенюк, О. В. (2019). Переваги і недоліки політики мультикультуралізму. Форум Права, 56(3). 6–12. DOI: http://doi.org/10.5281/zenodo.3240906.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; політика мультикультуралізма; мультикультуралізм; полікультурне суспільство; міжкультурний діалог; соціокультурний конфлікт; мультикультурализм; поликультурное общество; межкультурный диалог; социокультурный конфликт; politics; multiculturalism; multicultural society; intercultural dialogue; socio-cultural conflict